Effects of L-citrulline supplementation and watermelon intake on arterial stiffness and endothelial function in middle-aged and older adults: a systematic review and meta-analysis of randomized controlled trials - Luo, Ping; Li, Ziyi; Liu, Kang; Gao, Weifeng (Frontiers in Nutrition, 2025)
ObjectivesTo determine and explore the effects of L-citrulline supplementation and watermelon intake on arterial stiffness (AS) and endothelial function in middle-aged and elderly individuals.ParticipantsMiddle-aged and elderly adults.DesignsA systematic review and meta-analysis of randomized controlled trials (RCTs).MethodsA comprehensive search was conducted across four major electronic databases (PubMed, Cochrane, EMBASE, and Web of Science), covering the period from database inception to May 1, 2025. The quality of included studies was assessed using the Cochrane Risk of Bias Assessment tool 2.0. Data analysis was performed with RevMan 5.4.1 software; pulse wave velocity (PWV) data were analyzed using a random-effects model to pool effect sizes, while flow-mediated dilation (FMD) data were analyzed using a fixed-effects model to pool effect sizes. Heterogeneity was evaluated using the chi-square-based Cochran's Q test (p < 0.10) and the I2 statistic.ResultsThis systematic review and meta-analysis included 8 RCTs with a total of 176 participants. The results showed that L-citrulline supplementation significantly improved FMD [1.81 (95% CI: 0.76 to 2.85), p = 0.0007]. Although L-citrulline supplementation did not significantly improve PWV [−0.14 (95% CI: −0.45 to 0.17), p = 0.37], a trend toward improvement was observed. Subgroup analyses indicated that L-citrulline supplementation had the most significant effect on ankle-brachial pulse wave velocity (BA-PWV) [−1.11 (95% CI: −1.37 to −0.85), p < 0.00001). However, watermelon supplementation did not significantly improve PWV and FMD in middle-aged and older adults.ConclusionSupplementation with L-citrulline has a positive impact on vascular function in middle-aged and elderly individuals, significantly improving FMD. However, although there was no improvement in PWV, subgroup analysis results still show that L-citrulline supplementation significantly reduced BA-PWV. This suggests that this intervention may have potential application value in preventing and improving the risk of cardiovascular diseases (CVDs) in this population. However, watermelon intake did not significantly improve FMD and PWV in middle-aged and older adults, and there is insufficient relevant literature. Future large-scale studies are needed to confirm the effects of watermelon on vascular function.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/CRD420251052954